Um Caso de Mania após Tratamento com CPAP em Doente com Apneia Obstrutiva do Sono - Lobo, Margarida (2014)
Obstructive slee apnoea (OSA) is a common sleep disorder. It has been recognized a link between OSA and depression , which is most of the times resistant to treatment. Other aspects of OSA are metabolic: insulin resistance, hypertension and obesity. A common treatment for OSA is Continuous Positive Airway Pressure (CPAP). This treatment may reverse the cognitive and affective dysfunction but in some cases with residual impairment. The author reports a case of a 48 years old man with family history of bipolar disorder but no past history of psychiatric disorders. A diagnosis of OSA led to the use of CPAP. Ten days later he started hypomanic symptoms and 15 days later he was strongly manic. He was hospitalized and treated with olanzapine, lorazepam and divalproate. CPAP treatment was interrupted. After recovery the patient became depressed and, since then, although he doesn't meet the criteria for major depression, depressive symptoms persisted even with olanzapine and lamotrigibne. Meanwhile he was diagnosed with diabettes mellitus 2 and olanzapine was discontinued and he was put on ziprasidone. The author discusses the contribution of the OSA and treatment with CPAC to the appearance and maintenance of the affective disorder in a patient with family susceptibility. The discussion also includes the metabolic aspects of OSA that can be worsened with the medication to control the affective disorder.